Novel resistor-capacitor (RC) network-based capacitance signal conditioning circuit for tip clearance measurement on gas turbine engine. (February 2020) - Satish, TN; Vivek, A; Anagha, SN; Rao, ANV; Uma, G; Umapathy, M; Chandrasekhar, U; Kiran, G
Blade tip clearance is a critical engine health parameter measured on gas turbines. Increase in tip clearance results in decreased efficiency, whereas with decrease in clearance due to thermal and centrifugal loads, rotor blades might rub the engine case. Various sensing techniques are being used, among them, capacitance-based systems are widely used by many engine houses. Among the capacitance conditioning circuits, resistor-capacitor series network-based circuits are simple to implement but pose many challenges during practical development. During the current work, the authors have designed a novel capacitance conditioning circuit combining resistor-capacitor series network, instrumentation amplifiers, and direct current–direct current converters. Performance of the developed capacitance conditioning electronics was evaluated through lab testing and tip clearance measurement on fan stage of an aero gas turbine engine. The prototype conditioner circuit has efficiently conditioned and resolved small capacitances varying from 1.25 pF to 0.00413 pF for running clearances between 0.4 mm and 3 mm, respectively. The developed electronics produced high output with signal-to-noise ratio of 58.1 dB, resolution of 2.5 µm, bandwidth of about 700 kHz, and an accuracy of about 98%. This development has culminated towards miniaturization of the total electronics and has the potential to get developed as smart capacitance sensor. This paper explains the practical aspects and challenges involved while designing and developing such practical conditioning circuits.